1987
DOI: 10.1007/bf02623588
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of rabbit myometrial cells in primary culture: Influence of estradiol and progesterone treatment

Abstract: Myometrial cells were obtained following a three-step enzymatic digestion of uterine horns from Day 1 pseudopregnant rabbits. Isolated cells were cultured in RPMI 1640 supplemented with 10% fetal bovine serum (FBS), whole or steroid depleted (FBS-DC) at a plating density of 0.5 X 10(6) cells/ml. The cells reached confluency on Day 6 to 7 with whole serum and on Day 7 to 8 with DC serum. The process yielded myometrial cells at a purity level of at least 80% as assessed by indirect immunofluorescence using desmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Prior to chemical exposure, cells were grown in 5% charcoal-stripped calf serum in phenol red-free Dulbecco's modified Eagle's medium containing 1 nM insulin for a minimum of 5 days. This procedure was necessary to eliminate steroids normally found in serum (29). When cultures reached confluence, they were rinsed with Dulbecco's modified Eagle's medium and exposed to either TCDD, 17␤-estradiol, or their analogs, dissolved in Me 2 SO unless otherwise stated.…”
Section: Materials-tcddmentioning
confidence: 99%
“…Prior to chemical exposure, cells were grown in 5% charcoal-stripped calf serum in phenol red-free Dulbecco's modified Eagle's medium containing 1 nM insulin for a minimum of 5 days. This procedure was necessary to eliminate steroids normally found in serum (29). When cultures reached confluence, they were rinsed with Dulbecco's modified Eagle's medium and exposed to either TCDD, 17␤-estradiol, or their analogs, dissolved in Me 2 SO unless otherwise stated.…”
Section: Materials-tcddmentioning
confidence: 99%
“…Stromal cells have a greater proportion of a 42,000 MW protein that corresponds to actin; this may be related to their fibroblastic shape. Comparison of these cells with uterine smooth muscle, which also shows fibroblastic shapes using antidesmin antibodies, revealed distinct identity of each cell type (Boulet and Fortier, 1987). Epithelial cells, on the other hand, have at least four specific proteins between 40,000 MW and 60,000 MW that are not found in stromal cells.…”
Section: Discussionmentioning
confidence: 97%
“…Whole cellular proteins or cytoskeleton extracted as described elsewhere (Boulet and Fortier, 1987) were solubilized for 5 min a t 95°C in Laemmli's sodium dodecyl sulfate (SDS) buffer (Laemmli, 1970) at 0.5 pg/ml approximately protein concentration. Solubilized protein (5 pg for silver nitrate and 50 mg for Coomassie Brilliant Blue staining) were loaded on 12% Thomas and Kornberg SDS-polyacrylamide gels.…”
Section: Electrophoresismentioning
confidence: 99%
“…hCG treatment of virgin females does not modify the original pattern of NM myosin distribution in myometrial SMC. Since estrogens are involved in cellular proliferation (Travers and Knowler 1987) and probably induce the division of myometrial SMC both in vivo (Kirkland et al 1979;Mukku et al 1981) and in vitro (Boulet and Fortier 1987), it is tempting to speculate that the expression of this isoform is related to cellular hyperplasia. Cavaillé et al (1995) have reported that in human myometrium the expression of the 198-/200-kDa B-type NM-MyHC isoform correlated with neoproliferative phenomena, but not with changes in the growth pattern observed during pregnancy.…”
Section: Discussionmentioning
confidence: 99%